A contribution to the knowledge of scolopendromorph centipedes of Martinique Island, with descriptions of two new species (Chilopoda: Scolopendromorpha) - Schileyko, Arkady; Iorio, Etienne; Coulis, Mathieu (Zootaxa, 2018)
The paper provides new data on seven scolopendromorph centipede species collected in Martinique Island. Two new species are described: Otostigmus (Parotostigmus) salticus n. sp. and Cryptops (Trigonocryptops) martinicensis n. sp.; their systematic position is discussed. Notes on the system of subgenus Trigonocryptops Verhoeff, 1906 are given and Cryptops sarasini var. furcata Ribaut, 1923 is confirmed as subspecies. Cormocephalus guildingii Newport, 1845, Newportia longitarsis guadeloupensis Demange, 1981 and N. pusilla Pocock, 1893 are reported from Martinique for the first time. A list of the Scolopendromorpha of this island is given.